Building Communities Through Islamic Social Finance: The Role of Philanthropy for Economic Development - Izniyah Izniyah (Islamic Economic Management & Entrepreneurship, 2026)
This paper examines the role of philanthropy in community development through Islamic social finance for sustainable economic development. This study highlights the importance of Islamic social finance as a powerful instrument for financial inclusion, poverty alleviation, and improving general welfare. This study uses a qualitative approach with data collection through interviews, literature review, and documentary analysis. The results show that philanthropy in Islamic social finance plays a significant role in community development by encouraging economic independence, empowering individuals and groups, and promoting the principles of social justice. In the context of economic development, Islamic philanthropy also makes significant contributions to job creation, increasing access to capital for micro and small businesses, and supporting innovation and sustainable business development. These findings provide valuable insights for practitioners, decision-makers, and financial institutions to understand and harness the potential of philanthropy in Islamic social finance to achieve inclusive and sustainable economic development.